(3GdfcJ GdCKQjI Ydi GdCMGOjK GdLRQjIs - (3TeS GdOjf eMeO Hf YHO Gddg Hf eMeO GdbjSi GdOeTbj GdeYQha HGHf fGUQ GdOjf,J (B842 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO abO hbaJ Ydi LRA NQLg HYV GdCFeI GdYUQjjf dfaSg hCHQRg GdWGdHjf HQhR GdfgGQ HTeSg s
(3BNQgG (B:s
(3GdbGSe Hf YHO GdQMef GdOeTbi UGMH GYLGjH ajeG PcQg CMeO Hf MfHd hgPG efgG hGddg JYGdi CYde BNQ GdfcJ GdCKQjI Ydi GdCMGOjK GdLRQjI s
(3cJHJ HNW eged GdfbW CMjGfkG fbdkG Yf fSNI HNW GdeDda s
(3hYdi MGTjI fSNJfG gPg SeGY HNW GdeDda hHBNQgG SeGY (B836 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN faSg hTgjO GdeDda Ydi gPG GdSeGY hELGRI HNWg s
(3HgG fXGe GdJYbjHIs
(3hUaMI GdZdGa CjVkG HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdMOjK h GdeUWdMs